ANALISA DAN MITIGASI RISIKO SUPPLY CHAIN DENGAN PENDEKATAN MODEL HOUSE OF RISK PADA PERUSAHAAN XYZ - Hady Sofyan; Akhsani Nur Amalia; Daffa Pratama Akmal; Rizky Fajar Ramdhani (Jurnal Teknologika, 2022)
Abstract. XYZ Company is a company engaged in the food service industry that produces various types of products such as food, spices, flour, etc. The production process, starting from raw materials until the products are sent to consumers, there are still many risks that interfere with industrial activities that do not run smoothly. The steps taken to identify and measure the potential risks that exist in supply chain at XYZ Company are using the house of risk (HOR) model. This model is a framework developed by Laudine H. Geraldin and I. Nyoman Pujawan by developing the FMEA (Failure Mode and Effect Analysis) method and the QFD (Quality Function Deployment) method. The identified risk events have the potential to arise in the supply chain of XYZ Company, namely in Plan activities there are 4 risks, source there are 5 risks, make activities have 9 risks, delivery activities have 5 risks, and in Return activities there are 3 risks. As many as 22 risk agents (risk agents) in the supply chain of Company XYZ were identified, which were then prioritized based on the ARP value of 5 risk agents, namely delaying the production process (A8), not being careful with production planning (A1), quality inspection errors (A17), Human Error (A5), Don't care about SOP (A22). Mitigation or prevention strategies that are prioritized to prevent the causes of risk are (in order) Increase the emphasis on SOPs to each line, Show the consequences of not meeting SOPs, namely work accidents, Improve employee abilities with good training or direction, Always emphasize employees to comply with SOPs, Motivate employees Making value stream mapping, briefing each employee that SOPs are important Conduct training for employees. Keywords: Risk Mitigation, Supply Chain Management, House of Risk